Interpretation of Verses on the 'Parable of the Deeds of Disbelievers': Embodied Islamic Knowledge in Ibn 'Ashur's Maqasid-Based Exegesis - Millah, Dhiya Atul; Nisa’, Khoirun; Albshkar, Hajer Abdallah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article examines the reinterpretation of verses depicting the